Differences in the presence of alkaloids and phenols in five informally traded muña samples from traditional markets in Lima - Peru - Pawer Pucurimay, Dalia (2018)
Objective: To demonstrate the presence of alkaloids and phenols in the Minthostachys mollis (muña) flower branch, and to compare the results with those of five informally traded muña samples bought in Lima - Peru. Materials and methods: A sample of Minthostachys mollis was collected in the department of Junín (located at 321 km from Lima and at 4113 m.a.s.l.), Peru, according to the Cerrate E. and Ramagosa et. al. method, and identified by a botanic specialist. Other five samples without sanitary registry were bought in different markets. The phytochemical screening was performed using the method proposed by Olga Lock, M.D. The qualitative references employed were "+++" (highly present), "++" (moderately present), "+" (slightly present) and "-" (absent). Results: Regarding the alkaloids, the sample of Minthostachys mollis showed "++" metabolites. In contrast, M1 showed no metabolites, M3 showed "+" metabolites, and M2, M4 and M5 showed "++" metabolites. Concerning the phenols, the sample of Minthostachys mollis showed "+++" metabolites. In contrast, M4 showed "++" metabolites, and M1, M2, M3 and M5 showed "+++" metabolites. Conclusions: In comparison with the sample of Minthostachys mollis, qualitative differences in the presence of the studied metabolites were demonstrated in the informally traded samples.